2017
DOI: 10.3390/molecules22101678
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Novel (Z)- and (E)-Verbenone Oxime Esters

Abstract: Twenty-seven (Z)- and (E)-verbenone derivatives bearing an oxime ester moiety were designed and synthesized in search of novel bioactive molecules. Their structures were confirmed by UV-Vis, FTIR, NMR, ESI-MS, and elemental analysis. The antifungal and herbicidal activities of the target compounds were preliminarily evaluated. As a result, compound (E)-4n (R = β-pyridyl) exhibited excellent antifungal activity with growth inhibition percentages of 92.2%, 80.0% and 76.3% against Alternaria solani, Physalospora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…scoparius flowering branches and flowers, as linalool, terpinen-4-ol or α -terpineol have well known phytotoxic activity, e.g., [ 34 , 61 ]. Also, verbenone, a semiochemical with reputed pest deterrent properties because of its ecological role as anti-aggregation pheromone (see [ 62 ] as a review), has very recently been explored for its phytotoxicity [ 63 ]. Verbenone is synthetically obtained from the abundantly available pinenes in pine oleoresins, and then commercially used in tree protection [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…scoparius flowering branches and flowers, as linalool, terpinen-4-ol or α -terpineol have well known phytotoxic activity, e.g., [ 34 , 61 ]. Also, verbenone, a semiochemical with reputed pest deterrent properties because of its ecological role as anti-aggregation pheromone (see [ 62 ] as a review), has very recently been explored for its phytotoxicity [ 63 ]. Verbenone is synthetically obtained from the abundantly available pinenes in pine oleoresins, and then commercially used in tree protection [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, only two recent studies dealt with the phytotoxicity of verbenone added to the culture solution [ 63 , 72 ]. These studies showed that verbenone applied at 100 to 150 μg mL -1 exerted extremely weak inhibition of the seedling growth of Echinochloa crus-galli and Brassica campestris [ 63 ], or just a delay on L . sativa germination [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Verbenone presents good repellent properties, as well as anti-inflammatory [277] and bronchodilator [278] activity. Verbenone derivatives present important biological characteristics such as antifungal [279], antiviral [280], antioxidant activities and (in cortical neurons) anti-ischemic properties [281]. Given these promising effects, Melo et al [282] evaluated the anticonvulsant activity of verbenone at doses of 150, 200, and 250 mg/kg (i.p.).…”
Section: (-)-Verbenonementioning
confidence: 99%
“…In continuation of our long-term focus on natural product-based bioactive compounds [ 28 , 29 , 30 , 31 , 32 ], a series of novel nopol-derived 1,3,4-thiadiazole-thiourea compounds were synthesized by integrating bioactive 1,3,4-thiadiazole and thiourea moieties into the molecular skeleton of nopol. Structural characterization, antifungal evaluation, and structure–activity relationships of the title compounds were determined as well.…”
Section: Introductionmentioning
confidence: 99%